Investigating the Empirical Relationship Between Service Quality, Trust, Satisfaction, and Intention of Customers Purchasing Life Insurance Products - Panigrahi, Shrikant; Noor Azlinna, Azizan; M., Waris (Informatics Publishing Limited, 2018)
The purpose of this paper was to identify the key SERVQUAL factors for consumer purchase intention in the context of life insurance products in Malaysia. The study was performed based on primary data using a self-administered questionnaire from the Klang valley region of Malaysia. Using a cross-sectional study, a total of 215 usable responses were collected using convenience sampling technique. To measure customer satisfaction, trust, and purchase intention, seven key SERVQUAL factors were utilized, that is, tangibility, reliability, responsiveness, assurance, empathy, helpfulness, and problem solving. Data were analyzed using a 5-point Likert scale. Descriptive statistics & exploratory and confirmatory factor analysis were employed. The findings revealed that customer satisfaction and trust together with SERVQUAL factors lead to purchase intention. Conversely, this paper also found that life insurance agents with problem-solving skills and helpfulness will lead to an increase in customers' intention to purchase life insurance products. From the validation of the framework, it is obvious to make sure that all the quality functions must be in accordance with increasing competitive advantage along with the organizational objectives.